Medical inquiries and city doctors in the late Medieval Milan: a study of the Libri Mortuorum of 1478 (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
The analysis of the Libri Mortuorum, mortuary registers redacted by the Officio di Sanità of Milan, is at the foundation of this paper for a study of the socio-sanitary situation of the city and of the medical-scientific knowledge of the time. Taking as an example the year 1478, I decided to gather and elaborate the data concerning mortality and demography of Milan during the Sforza’s rule. Acknowledging as their primary role the control and prevention of epidemics, I chose to address the activity of Milanese physicians, especially two, facing the possibility of contagious outbreaks. Finally, I focused directly on who those specialists in medicine were and what their role in the field of the late Fourteenth’ Milanese health care was.
Keywords: Physicians; Plague; Officio di Sanità; Millan; Epidemics; Illnesses